METHODOLOGY FOR THERMAL SIMULATION OF ELECTRONIC DEVICES WITHOUT KNOWING THE THERMAL DISSIPATION - Sousa, Reginaldo; Tabone, Amarildo [UNESP]; Shinoda, Ailton [UNESP]; Gregolin, Rafael; Gomes, JFS; Meguid, S. A. (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2016)
Electronic components with high thermal dissipation, can cause serious problems for the developed product. The electronic components are limited by the maximum operating temperature, this characteristic is called junction temperature. If the junction temperature is exceeded, the component will present inadequate behavior or may be damaged. Ideally, the electrical design and thermal design go together in the development of equipment, in order to obtain an optimized product. The problem is that in many cases there is an enormous difficulty to meet the thermal power dissipated of electronic components, not of resistors or capacitors, but integrated circuits that have inside, a very complex structure containing thousands or millions of transistors. The objective of this work is to present a methodology that is based into numerical correlations and practical tests, to know the temperature field in electronic devices without the knowledge of the power dissipation.
Keywords: Thermal simulation; power dissipation; numerical correlation; integrated circuit